Answer:
x = 7 x = -6
Step-by-step explanation:
x^2−x−42=0
Factor
What two numbers multiply to -42 and add to -1
-7*6 = -42
-7+6 = -1
(x-7) (x+6) =0
Using the zero product property
x-7 =0 x+6 =0
x = 7 x = -6
1,2,3,4,6,8,12,24 are all the factors to 24
N=#
-6(n)
I think this is the answer
Given:
2x - 3y = -6 ⇒ identified as 1st equation
x + 2y = 8 ⇒ identified as 2nd equation
Let us first get the value of x using the 2nd equation.
x + 2y = 8
x = 8 - 2y
Substitute x in the 1st equation with its value and find the value of y.
2x - 3y = -6
2(8-2y) - 3y = -6
16 - 4y -3y = -6
-4y - 3y = -6 -16
-7y = - 22
y = -22/-7
y = 22/7 simplified to 3 1/7
Substitute the value of y in the 2nd equation.
x = 8 - 2y
x = 8 - 2(22/7)
x = 8 - 44/7
x = (8 * 7/7) - 44/7
x = 56/7 - 44/7
x = (56-44)/7
x = 12/7 simplified to 1 5/7
To check: x = 12/7 and y = 22/7 *we need to use the improper fractions.
2x - 3y = -6
2(12/7) - 3(22/7) = -6
24/7 - 66/7 = -6
(24-66)/7 = -6
-42/7 = -6
-6 = -6
x + 2y = 8
12/7 + 2(22/7) = 8
12/7 + 44/7 = 8
(12+44)/7 = 8
56/7 = 8
8 = 8
3(x+1) = 2(x-8) + 3. First, remove the parentheses by distributing (multiplying out the numbers):
3x + 3 = 2x - 16 + 3.
Then, combine any like terms on the same side of the equals sign;
3x + 3 = 2x -13.
Then, move the like terms on opposite sides of the equals sign to the same side of the equals sign (don't forget to change the signs)..
3x -2x = -13 - 3.
Then combine the like terms on the same side of the equals sign again.. x = -16 .